Grit Character of High School Students in the Digital Era - Fitri Aulia; Ni Ketut Suarni; Kadek Suranata; I Ketut Gading (Journal of Current Studies in SDGs, 2027)
Objective: The study aims to analyze the grit character of high school students in the digital era. The study emphasizes the importance of persistence, consistency, and determination among students in facing learning challenges caused by rapid technological development. This research contributes to Sustainable Development Goal (SDG) 4 by highlighting the importance of developing student character to support quality education in the digital era. Method: The research employed a quantitative approach with an ex-post facto research design. The research population consisted of eleventh-grade students at SMA N 1 Montong Gading, East Lombok. Data were collected using a grit questionnaire consisting of two dimensions: consistency of interest and perseverance of effort. The sample consisted of 23 students selected using proportionate stratified random sampling.  Results:  The results showed that the grit character of students in the digital era was categorized as good, with an average score of 74.71%. Students demonstrated persistence, enthusiasm, creativity, and responsibility in completing digital-based learning tasks, including multimedia video assignments. The findings indicate that digital technology can support students’ learning processes when accompanied by strong character development.  Novelty: The study provides new insights into student grit characteristics in the context of digital interaction culture among high school students in East Lombok. The findings highlight the importance of integrating digital literacy and character education to strengthen students’ resilience and learning achievement in supporting SDG 4.